A randomised controlled trial of oral misoprostol vs injection methylergometrine for prevention of post partum hemorrhage - Patil, Neelamma B.; Patted, Shobhana S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To compare the efficacy of 600mcg of oral misoprostol with 0.2mg of injection methylergometrine for the prevention of post partum hemorrhage. Methods: 200 apparently normal pregnant women were randomized to receive either 600mcg of oral misoprostol (study group) after delivery of baby or 0.2 mg of methylergometrine intravenously (control group) after delivery of placenta. Primary outcome was to know the incidence of post partum hemorrhage in both the groups. Secondary outcome measures were to look for mean blood loss, need for any other uterotonic agents, need for blood transfusion, need for surgical intervention, mean duration of third stage and side effects of both the drugs. Results: Out of 200 cases, two cases were excluded for the final analysis. Incidence of PPH was 9% in misoprostol group & 6% in methylergometrine group which was not significant (p >0.05). There were no significant differences among both the groups in mean blood loss, duration of bleeding, need for further oxytocics and duration of third stage. Shivering was significantly more common in misoprostol group (36% Vs 2% p< 0.0027). Conclusion: Efficacy of 600mcg of oral misoprostol is comparable to injection methylergometrine 0.2 mg intravenously for prevention of post partum hemorrhage. So, in settings where methylergometrine is used routinely for prophylaxis, oral misoprostol can be used with more ease & other advantages over injectables. Significantly more number of patients in misoprostol will have shivering as a major side effect, which should be kept in mind.